Mental Health in Inuit Youth from Nunavik: Clinical Considerations on a Transcultural, Interdisciplinary, Community-oriented Approach - Auclair, Geneviève (Canadian Academy of Child and Adolescent Psychiatry, 2012)
OBJECTIVE: This paper discusses the organization of mental health care for youth in Nunavik and considers how best to adapt care to the sociocultural and geographical specificities of this region. METHOD: Services are described and discussed by a general practitioner and a community worker in Nunavik. RESULTS: Current social and medical care delivery in Nunavik is provided by professionals who are largely non-Inuit and who are supported by Inuit community workers and interpreters. Community workers are key players in the provision of social and mental health care for youth. Efforts are made to adapt care to the sociocultural specificities of Inuit youth, and to locally-based multidisciplinary care addressing the multiple determinants of mental health. CONCLUSION: While efforts to adapt care are ongoing, the ideal model of care integrating transcultural, multidisciplinary and community-oriented approaches are yet to become a reality. Increased communication among care providers is suggested as a way to strengthen the current collaborative model of care. Future goals include having a majority of care being provided locally and building community ownership and governance of care institutions.